A Kinetic Study of Iron(II) Reduction of Cobaloxime by Visible Spectrophotometric Method - Dayalan, A.; Balakrishna, R. (Asian Journal of Chemistry, 2016)
The kinetics of iron(II) reduction of aquoiodocobaloximes, viz., [Co(dmgH)2(H2O)I] where dmgH– = dimethylglyoximato mono anion, was studied spectrophotometrically at 484 nm in 4% (v/v) DMSO-H2O medium at 27 ± 0.1 °C at various hydrogen ion concentrations and ionic strength under pseudo-first-order conditions using an excess of the reductant. The inverse dependence of rate on [H+] suggests equilibrium between the protonated and unprotonated forms of the complexes, the protonated form reacting slower than the unprotonated form. Added Ni2+ and ionic strength have no effect on the rate of the reaction.